Anthropometrical, physical, motor and sport psychological profile of adolescent males with sprinting potential - Kruger, A.; Pienaar, A. E. (South African Journal for Research in Sport, Physical Education and Recreation, 2016)
This study determined whether anthropometrical, physical, motor and sport psychological differences exist between a group of male adolescents who show talent for sprinting and their less talented counterparts. Grade 8 boys (N=89; mean age: 13.25±0.46 years), from a high school in Potchefstroom voluntarily participated in the study. A general talent identification (TID) protocol and a sport psychological questionnaire were completed. The 40m-sprint test was used to categorise the subjects into two groups. Those in the top 10% were assigned to the talented group (TG) (n=8, mean age=13.79), and the remaining subjects were assigned to the less talented group (LTG) (n=72, mean age=13.55). An analysis of covariance (ANCOVA) was applied with stature as the covariate to adjust for variations in growth status between the two groups. The practical significance of differences between the two groups was determined by means of effect sizes (ES). The level of significance was set at p=0.05. Significant differences with the potentially talented sprinters, who obtained better scores in upper and lower body explosive power, acceleration, maximal speed, aerobic endurance and in goal setting were found.